Determination of isoflavones in soy bits by fast column high-performance liquid chromatography coupled with UV-visible diode-array detection - Klejdus, Borivoj; Mikelová, Radka; Petrlová, Jitka; Potesil, David; Adam, Vojtech; Stiborová, Marie; Hodek, Petr; Vacek, Jan; Kizek, René; Kubán, Vlastimil (Journal of chromatography. A, 2005)
A fast determination of isoflavones (genistin, genistein, daidzein, daidzin, glycitin, glycitein, ononin, formononetin, sissotrin and biochanin A) by HPLC/UV-vis-DAD working at 254 nm is described. An Atlantis dC18 fast reversed-phase chromatographic column (20 mm x 2.1 mm, 3 microm particle size) was used at a flow rate 0.35 ml min(-1) of a mobile phase consisted from 0.1% (v/v) acetic acid (A) at pH 3.75 and methanol. (B). A linear gradient profile was used for separation at the column temperature 36 degrees C. Limits of detection (LODs for 3 S/N criterion) per sample injection (5 microl) ranged from 166.2 to 17.0 fmol (9.4-1.1 ng ml(-1) for biochanin A and genistin, respectively. The recoveries 96-106% were obtained for the different concentrations of the isoflavones (RSDs 2-8%). The pressurized liquid extraction/HPLC/UV-vis-DAD method was used for the determination of the isoflavones in soy bits (28-962 microg g(-1) dry weight). The proposed procedure is faster (ca. 8 min) without loosing its separation efficiency (up to 10 isoflavonoids can be determined) and sensitivity (tens to hundreds fmol).
Keywords: ultrafialové záření; isoflavony; Glycine max; Temperature; Ultraviolet Rays; Chromatography, High Pressure Liquid; vysokoúčinná kapalinová chromatografie; teplota; Isoflavones